Pengaruh Lingkungan Kerja dan Budaya Organisasi Terhadap Loyalitas Kerja Karyawan Whiz Prime Hotel Kota Padang - Aldiman, Aldiman; Abrian, Youmil; Andres, Fran Serano (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2023)
This research was conducted of this research is the work loyalty of Whiz Prime Hotel Padang employees which is influenced by the work environment and organizational culture. The aims of this study: 1) To know the effect of work environment and organizational culture on employee loyalty, 2) to describe work environment, 3) to describe organizational culture, 4) to describe employee loyalty. And the type of research used is quantitative research with a causal associative approach. The research was conducted at Whiz Prime Hotel Padang. For the population of this study as many as 62 people. And for the selection of this research sample, namely a saturated sample with a total of 62 people. And the data collection technique used is the Likert Scale which has been tested for its validity and reliability. The analysis technique of this study used multiple linear regression analysis which was processed with the help of the SPSS version 26.00 program. So the results of the study show that 1) There is a significant influence of the work environment and organizational culture on employee loyalty by 55.7%, 2) the work environment is in the fairly good category with an achievement score of 45%, 3) Organizational culture is in the category quite good with an achievement score of 42%, 4) Employee Loyalty is also in the fairly good category with an achievement score of 36%.